Formation of the New Forms of Management Systems Spatially Localized Economies in the Paradigm of the Cluster Approach - Sozinova, Anastasiya A.; Androsova, Irina V.; Ðbramov, Valery L.; Tikhomirov, Evgeny A.; Redin, Dmitri V.; Oganesyan, Tigran L. (International Review of Management and Marketing, 2016)
The analysis of scientific papers showed that many scientists pay considerable attention to the study of various aspects of the effectiveness of new models of business management in the formats of industries and regional economies. At the same time remain insufficiently studied problems of formation of organizational and economic instruments of the cluster approach, taking into account sectoral and regional specificities of the territories. In addition, it should be noted lack of practical research on evaluating the effectiveness of cluster management in an uncertain environment. Therefore, the need to strengthen the scientific component in the functional verification of the effectiveness of organizational and economic development tools cluster management technologies based on the analysis of factors external and internal environment of the regional economic system determined the direction of the research thesis and justification of its goals and objectives. Keywords: management system, cluster, regional economy JEL Classifications: G3; P25